The Influence of Transformational Leadership and Transactional Leadership on Motivation Moderated by Reward on Employee Performance (Study on Cv. Galaxy Mega Indah) - A.K Rafifil Umam (Universitas Ciputra Surabaya, 2022)
Galaxy Mega Indah is a company engaged in the distribution of consumer good products. In terms of performance, policies related to reward, work motivation, and leadership style in CV are needed. Mega Galaxy Beautiful. The purpose of the study was to test the influence of transformational and transactional leadership with work motivation on performance moderated by rewarding employees. This research is quantitative. The population and sample of the study constituted all 50 employees. Data analysis techniques using SEM-PLS with Smart-PLS 3.0 and SPSS 23 software. Hasil research concluded that: (1) Transformational leadership does not have a significant effect on the work motivation of CV employees. Galaksi Mega Indah; (2) Transactional leadership has no significant effect on the work motivation of CV employees; (3) Rewarding does not moderate the effect of transformational leadership on the work motivation of CV employees. Galaksi Mega Indah; (4) Reward provision does not moderate the effect of transactional leadership on the work motivation of CV employees; and (5) Work motivation has a significant positive effect on the performance of CV employees. Mega Galaxy Beautiful.